Output Response to Currency Crises - Sahay, Ratna (International Monetary Fund, 2003)
This paper analyzes the behavior of output during currency crises using a sample of 195 crisis episodes in 91 developing countries during 1970-98. It finds that more than two-fifths of the crises in the sample were expansionary, and that output contraction was greater in large and more developed economies than in small and less developed economies. Currency crises have not been any more contractionary in the 1990s than in the previous two decades. Countries that traded less with the rest of the world, that had a relatively open capital account, and where crises were preceded by large capital inflows were more likely to be associated with contraction during crises. The contraction was more pronounced if trade competitors devalued, oil prices rose during the crisis, and postcrisis period was marked by tight monetary policy and expansionary fiscal policy